Machines with non-conventional topologies for more electric applications - Dusek, Jiri (2017)
This thesis investigates the design, performance and fault tolerant capability of electric machines with unconventional topologies used in more electric drive applications. Two different machine topologies are analysed: Flux reversal permanent magnet machine and a field wound flux switching machine.